The effects of platelet-rich plasma on the osteogenic induction of bone marrow mesenchymal stem cells. (16th June 2014) - Zou, Jun; Yuan, Chenxi; Wu, Chunshen; Cao, Cheng; Yang, Huilin
Abstract: Bone marrow mesenchymal stem cells (BMSCs) are multipotent stem cells. Finding methods to improve the osteogenic potential of these cells is a key factor in bone tissue engineering. Platelet-rich plasma (PRP) contains powerful growth factors that produce changes in a variety of cell types. The purpose of this study was to explore the effects of PRP on the osteogenic differentiation of BMSCs in vitro . Rabbit BMSCs were harvested and cultured in vitro in control media or in media enhanced with PRP. BMSCs began to attach 12–24 hours after seeding. A MTT assay demonstrated that PRP-induced BMSCs grew rapidly compared with the control group. The PRP group also showed strongly positive staining of alkaline phosphatase and mineralized nodules whereas the control group showed negative staining. However, the alkaline phosphatase activity and the mRNA level of the osteogenic markers (osteocalcin and osteopontin) remained higher in the PRP group. These results confirmed that PRP could enhance the proliferation of BMSCs and effectively promote the osteogenic differentiation of BMSCs in vitro .